2003
DOI: 10.1097/01.ju.0000067601.29966.4a
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Therapeutic Role for Post-Chemotherapy Retroperitoneal Lymph Node Dissection in Metastatic Transitional Cell Carcinoma of the Bladder?

Abstract: Retroperitoneal lymph node dissection can be safely performed for metastatic transitional cell carcinoma. Retroperitoneal lymph node dissection has curative potential, particularly in patients with viable tumor in no more than 2 lymph nodes after chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 16 publications
2
47
0
4
Order By: Relevance
“…[265][266][267][268][269] C. Recommendation for patients in whom newly diagnosed bulky nodes are found at time of laparotomy i.…”
Section: Discussionmentioning
confidence: 99%
“…[265][266][267][268][269] C. Recommendation for patients in whom newly diagnosed bulky nodes are found at time of laparotomy i.…”
Section: Discussionmentioning
confidence: 99%
“…17 Sweeney and colleagues reported on the resection of clinically detectable retroperitoneal nodes in 11 patients after response to chemotherapy. Seven patients eventually developed recurrence outside of the original surgical field while 4 (36.4%) patients were rendered free of disease as a result of surgical consolidation.…”
Section: Non-regional Nodal Dissectionmentioning
confidence: 99%
“…Cowles et al, writing on the concept of surgical treatment for metastatic urothelial cancer, reported a median 5-year survival rate for six patients following thoracotomy for solitary pulmonary metastatic lesion [7]. Due to the promising responses to chemotherapy, the therapeutic concept of surgery for metastatic urothelial cancer has been addressed again, a decade after the initial reports [8][9][10][11][12][13][14]. These reports support the therapeutic approach by surgical resection of metastatic lesion in patients with metastatic urothelial cancer.…”
Section: Introductionmentioning
confidence: 70%
“…Recently several authors have reported on the benefits of surgical resection of metastatic sites during a multidisciplinary approach for metastatic urothelial cancer [8][9][10][11][12][13][14]. Dodd et al [8] reported that a 5-yr overall survival rate of 33% was achieved in 50 patients with a major response to initial chemotherapy.…”
Section: Discussionmentioning
confidence: 99%